Bridging Need-Support Dimensions to Athlete’s Intentions to Continue Sports through Enthusiastic and Constrained Commitment: An Empirical Study in China - Bo ZHANG; Liang Fen YU (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The choice of continuing to participate in sports and physical activities for athletes is impacted by many social and economic factors; however, the support that players get is an important indicator of their sport continuing intentions and motivations. The following research study aims to analyze the impact of certain need support factors on the continuing intentions of athletes in China. Moreover, it also aims to examine the mediating role of enthusiastic commitment and the constrained commitment of the athletes. In this case, the researcher collects the requisite information with the help of a survey questionnaire in which a total of 438 participants is selected for the research study as a sample size that has some experience in athletics and were of Chinese ethnicity. The process of data analysis is conducted with the assistance of several techniques and tests like rotated component matrix, KMO and Bartlett’s test, confirmatory factor analysis, correlation analysis and structural equation modeling. The results of the research study shows that direct impact of autonomy support and relatedness support is significant and positive on intentions of continuing and the mediation of constrained commitment is full, while that of enthusiastic commitment is partial. The researcher has also included the overall implications and contributions of the study and the limitations of the process so that future scholars and researchers can further build on them in their work.